2013
DOI: 10.4236/ojst.2013.39079
|View full text |Cite
|
Sign up to set email alerts
|

Dysphagia in head and neck cancer: A review

Abstract: Head and neck cancers are frequently associated with dysphagia. Both pre-treatment and post-treatment etiologies have been described in the literature. The result of dysphagia has been well-documented as causing reductions in both quality-of-life and physical wellbeing. The goal of this review is to consolidate the current understanding of the relationship between head and neck cancers and dysphagia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…The severity of symptoms due to suppression of the thyroid gland is directly related to the size of the gland. 14 In this study, the most commonly found tumor stage group was T3 to T4, with as many as 36 people (90%), compared with 4 people (10%) in the T1 to T2 tumor stage group. This is in contrast to a similar study conducted by Carlson et al, using the Swedish version of the MDADI, which reported a distribution of 47 (55%) subjects in the T0 to T2 tumor stage group,compared with 38 subjects (45%) in the T3 to T4 tumor stage group.…”
Section: Discussionmentioning
confidence: 57%
See 4 more Smart Citations
“…The severity of symptoms due to suppression of the thyroid gland is directly related to the size of the gland. 14 In this study, the most commonly found tumor stage group was T3 to T4, with as many as 36 people (90%), compared with 4 people (10%) in the T1 to T2 tumor stage group. This is in contrast to a similar study conducted by Carlson et al, using the Swedish version of the MDADI, which reported a distribution of 47 (55%) subjects in the T0 to T2 tumor stage group,compared with 38 subjects (45%) in the T3 to T4 tumor stage group.…”
Section: Discussionmentioning
confidence: 57%
“…When dysphagia occurs, there will be manifestations, such as an increase in aspiration due to vocal cord or epiglottic dysfunction during the pharyngeal swallowing process. 14 Thyroid disease is a common cause of dysphagia. In one study, among patients who underwent thyroidectomy, dysphagia was the most common preoperative complaint.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations